Anxiety and depression among caregivers of inpatients suffering from chronic debilitating and terminal illnesses - Anandi, Basavakumar S.; Dhadave, Meenakshi M. (International Journal Of Community Medicine And Public Health, 2018)
Background: Depression and anxiety are the priority conditions covered by WHO’s Mental Health Gap Action Programme. Depression is a common illness worldwide, despite effective treatments available, fewer than half of those affected receive such treatments. Caregivers of the patients, attributed to bear higher burden of personal, financial, family, and social problems are expected to be predisposed to psychological illness. Thus this study was undertaken with following objectives; i) to estimate prevalence of anxiety and depression and ii) to find associated factors for anxiety and depression among in-patient care givers of a tertiary care hospital. Methods: An observational study was undertaken in the cardio, neuro, medical and cancer in-patient setting, in a tertiary care hospital, of Kalaburagi district. Study was undertaken for 2 months from Dec-2017 to Jan-2018. Care-givers of all, receiving in-patient care were included in the study. The anxiety and depression levels were assessed using GAD-7 & PHQ-9 questionnaires respectively. Results: All in-patient care-givers had some degree of anxiety of which majority of them had severe level of anxiety (50%). Likewise, 96% of the subjects had some degree of depression, of which 40% of them had moderately severe level of depression. Severe levels of anxiety and depression were found to be high among 30-40 years age group. Conclusions: It is crucial to screen the care givers, especially females, for presence of anxiety and depression. This approach will help timely identification and proper management of these individuals.